PERAN TEKNOLOGI PENDIDIKAN DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Aridianti, Aridianti; Jannah, Miftahul; Gusmaneli, Gusmaneli (Sindoro: Cendikia Pendidikan, 2024)
Along with the times, technology in its development certainly brings changes to life, especially in the world of education which will also continue to experience development. This article aims to determine the role of educational technology in improving the quality of education in this progressive era. So it is hoped that educational technologists will no longer feel doubtful and interested in adapting and being able to take advantage of technology with all its benefits in educational life. In writing this article we use a literature review method (library research), where researchers collect materials related to research from books, journals, scientific articles, literature and mass media coverage by describing and describing the data. Based on the discussion, it can be concluded that educational technology was created to solve learning problems by facilitating and providing alternatives and new innovations in the world of education. That way educational technology can make it easier to achieve educational goals. Seiring dengan perkembangan zaman, teknologi dalam perkembangannya tentu membawa perubahan bagi kehidupan terutama dalam dunia pendidikan yang juga akan terus menerus mengalami perkembangan. Artikel ini bertujuan untuk mengetahui peran teknologi pendidikan dalam meningkatkan kualitas pendidikan di era yang penuh kemajuan ini. Sehingga diharapkan para teknolog pendidikan tidak lagi merasa keraguan dan tertarik untuk beradaptasi serta mampu memanfaatkan teknologi dengan segala manfaatnya dalam kehidupan pendidikan. Dalam penulisan artikel ini kami menggunakan motode tinjauan literatur (library research), dimana peneliti mengumpulkan bahan-bahan yang berkaitan dengan penelitian yang berasal dari buku, jurnal-jurnal, artikel ilmiah, literature dan pemberitaan media massa dengan cara mendeskripsikan serta menguraikan data tersebut. Berdasarkan pembahasan dapat disimpulkan bahwa teknologi pendidikan diciptakan untuk memecahkan permasalah belajar dengan cara memfasilitasi dan memberikan alternatif serta inovasi baru di dunia pendidikan. Dengan begitu teknologi pendidikan dapat mempermudah untuk mencapai tujuan pendidikan.